2001
DOI: 10.1007/s00439-001-0627-9
|View full text |Cite
|
Sign up to set email alerts
|

Armenian Y chromosome haplotypes reveal strong regional structure within a single ethno-national group

Abstract: Armenia has been little-studied genetically, even though it is situated in an important area with respect to theories of ancient Middle Eastern population expansion and the spread of Indo-European languages. We screened 734 Armenian males for 11 biallelic and 6 microsatellite Y chromosome markers, segregated them according to paternal grandparental region of birth within or close to Armenia, and compared them with data from other population samples. We found significant regional stratification, on a level grea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 58 publications
(53 citation statements)
references
References 41 publications
3
49
1
Order By: Relevance
“…The present-day distribution of haplogroup L-M11 is mostly confined to southern, central and western Asia; [23] it has been found only at low frequencies in populations of the Caucasus region and the Middle East and is absent in Palestinian and Syrian Arab. [11,[24][25][26][27] Overall, this study has shown that Y chromosomes typically linked with Jewish ancestry were not detected by the higher resolution analysis conducted in the present study. It seems more likely that Arab traders, who are known to have established long-distance trade networks involving some thousands of kilometres along the western rim of the Indian Ocean, from Sofala in the south to the Red Sea in the north and beyond to the Hadramut, India and even China from about 900 AD, [28] are more likely linked with the ancestry of the nonAfrican founding males of the Lemba/Remba.…”
Section: Discussioncontrasting
confidence: 59%
“…The present-day distribution of haplogroup L-M11 is mostly confined to southern, central and western Asia; [23] it has been found only at low frequencies in populations of the Caucasus region and the Middle East and is absent in Palestinian and Syrian Arab. [11,[24][25][26][27] Overall, this study has shown that Y chromosomes typically linked with Jewish ancestry were not detected by the higher resolution analysis conducted in the present study. It seems more likely that Arab traders, who are known to have established long-distance trade networks involving some thousands of kilometres along the western rim of the Indian Ocean, from Sofala in the south to the Red Sea in the north and beyond to the Hadramut, India and even China from about 900 AD, [28] are more likely linked with the ancestry of the nonAfrican founding males of the Lemba/Remba.…”
Section: Discussioncontrasting
confidence: 59%
“…The most distantly related R1a chromosomes, that is, both R1a* and R1a1* (inset, Figure 1), have been detected at low frequency in Europe, Turkey, United Arab Emirates, Caucasus and Iran 14,41 (Supplementary Table S1). The highest STR diversity of R1a1a*(xM458) chromosomes are observed outside Europe, in particular in South Asia (Figure 1, Supplementary Table S4), but given the lack of informative SNP markers the ultimate source area of haplogroup R1a dispersals remains yet to be refined.…”
Section: Phylogeographymentioning
confidence: 99%
“…16,17 In the efforts to gain a comprehensive understanding of the impact that complex historical migrations and events have had upon the genetic structure of populations, the human Y-chromosome has emerged as a highly effective tool. 18 Prior examinations of the paternal lineages within Armenia have revealed population-expansion times corresponding to the Neolithic emergence of agriculture, 19 as well as genetic affinities toward both Near Eastern and European populations; 20,21 results that are largely corroborated by mitochondrial DNA 22 and Alu insertion (PAI) studies. 23 It should be noted, however, that the above-mentioned patrilineal studies are hindered by their utilization of a limited set of Y-chromosomal markers that severely restricted their ability to define phylogenetic relationships.…”
Section: Introductionmentioning
confidence: 99%